Knowledge and Practise of Hand Wash Hygiene Among Dentists - A, ROSHAN; SANTHANAM, ARCHANA; G, SRIDEVI. (The journal of contemporary issues in business and government, 2021)
INTRODUCTION: Hand hygiene is a key method used to reduce the danger of infection and its spread. In the modern world hand hygiene includes hand cleaning, disinfection and surgical hand scrubbing. The aim of this study is to analyse the knowledge and practise of hand wash hygiene among dentists. MATERIALS AND METHODS: A descriptive cross sectional survey was conducted among 118 dentists through a self administered questionnaire from march - april 2020. The responses were collected, tabulated in excel sheet and analysed using SPSS software. Chi square test was used to analyze the level of knowledge on hand hygiene among dentists with statistical significance of P< 0.05. RESULTS: 58.72% Of the participants are aware of hand hygiene practices. 71.569% practise hand hygiene practises before and after procedure. 55.96% received formal training in hand hygiene in the last 3 years. CONCLUSION: The overall knowledge on hand hygiene tends to be moderate among dentists. From the present study, female dentists had good knowledge on hand hygiene and its practices compared to males.